Comparison of prepandemic and postpandemic students’ attitude to the electronic learning at universities with foreign language acquisition in mind - E. V. Zubareva; I. G. Tuchkova (Цифровая социология)
The article is devoted to the issues and problems connected with e-teaching of foreign languages for students in higher school. The results of pre- and post-pandemic surveys after two lockdowns which universities of the Russian Federation suffered from during 2019/2020 and 2020/2021academic years have been compared. The comparative analysis of pre- and post-pandemic students’ attitude to e-learning at the university on the whole and to foreign languages e-learning in particular has been weighed. The authors assessed students’ reaction to possible transition to e-learning, following gradual adaptation to new conditions during lockdown and the role of information technologies in e-learning. Aiming at fundamental analysis of distant learning the authors conducted students’ opinion surveys of the State University of Management on the issues of risks, disadvantages, convenience and advantages of the electronic and blended learning generally and on the issues of foreign language acquisition particularly. Besides, the attainments and skills that the students acquired during the periods of e-learning and which are, in students’ opinion, an essential part of their professional acquirements, have been studied.The article presents the results of postpandemic opinion survey, shows the main problems and advantages of electronic learning, reveals the types of foreign language activities, most recommendable for e-learning, makes conclusions about the advantages of the electronic and blended learning for foreign language acquisition in modern conditions. The conclusions about the necessity of the individual approach to each student even during e-learning have been made.